Pelatihan Jurnalistik sebagai Sarana Pengembangan Keterampilan Berpikir Kritis Mahasiswa Akademi Analis Kesehatan Pekalongan Jawa Tengah - Dimas Prasetya; Teddy Dyatmika; Ryan Marina; Hanif Ardiansyah (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
Critical thinking skills are skills that students need to have, especially in filtering various flows of information spread in the digital world. Apart from filtering information, this ability is especially important for students to be able to analyze and process various information circulating so that they can then make appropriate judgements. This helps students not to get lost in the circulation of existing information. This service program is a journalism training program for Pekalongan Academic Health Analyst (AAK) students with the aim of providing an understanding of the basics of journalism and using it to develop students' critical thinking skills. The results of this research show that students can understand the basics of journalism, especially in terms of reporting and publishing news, and students are also able to apply their journalistic understanding to practice and develop critical thinking skills through exploring news perspectives and solving problems in the reporting process.